Chromatin Remodeling Defects in Pediatric and Young Adult Glioblastoma: A Tale of a Variant Histone 3 Tail. (25th February 2013) - Fontebasso, Adam M.; Liu, Xiao‐Yang; Sturm, Dominik; Jabado, Nada
Abstract Primary brain tumors occur in 8 out of 100 000 people and are the leading cause of cancer‐related death in children. Among brain tumors, high‐grade astrocytomas (HGAs) including glioblastoma multiforme (GBM) are aggressive and are lethal human cancers. Despite decades of concerted therapeutic efforts, HGAs remain essentially incurable in adults and children. Recent discoveries have revolutionized our understanding of these tumors in children and young adults. Recurrent somatic driver mutations in the tail of histone 3 variant 3 (H3.3), leading to amino acid substitutions at key residues, namely lysine (K) 27 (K27M) and glycine 34 (G34R/G34V), were identified as a new molecular mechanism in pediatric GBM. These mutations represent the pediatric counterpart of the recurrent mutations in isocitrate dehydrogenases (IDH) identified in young adult gliomas and provide a much‐needed new pathway that can be targeted for therapeutic development. This review will provide an overview of the potential role of these mutations in altering chromatin structure and affecting specific molecular pathways ultimately leading to gliomagenesis. The distinct changes in chromatin structure and the specific downstream events induced by each mutation need characterizing independently if progress is to be made in tackling this devastating cancer.